Marketing : the core - Kerin, Roger A.; Hartley, Steven W. (New York McGraw Hill, 2022)
"Marketing: The Core utilizes a unique, innovative, and effective pedagogical approach developed by the authors through the integration of their combined classroom, college, and university experiences. The elements of this approach have been the foundation for each edition of Marketing: The Core and serve as the core of the text and its supplements as they evolve and adapt to changes in student learning styles, the growth of the marketing discipline, and the development of new instructional technologies"--
Includes index.
Ages 18+
Keywords: Marketing